Ᾱrā’ al-Qā’ilīn bi An al-Aṣl fī ‘Amal al-Mar’ah Khārij al-Bayt huwa al-Man’u wa Adillatuhum bayna Al-Naṣ wa Al-Ijtihād Dirāsah Taḥlīliyyah Naqdiyyah - Abd Allh Hash, Abd Al-Razaq (Jurnal Usuluddin, 2009)
Women’s involvement in public affairs and their participation in social responsibilities are among the essential themes of the Islamic contemporary thought. Many contemporary Muslim jurists and thinkers endeavour to answer some basic questions related to the social responsibilities and the social role of men and women to achieve social prosperity and civilizational progress of the society. They hold different answers to these questions. Some of them believed that woman is a partner of man in all aspects of life and both (man and woman) hold the same responsibility of social development and administration. On the other hand, there are those who rejected woman’s involvement in public affairs and said woman’s job is primarily to take-care of house and family affairs at home. Through textual and analytical methods, this paper attempts to evaluate the views of those Muslim jurists who restricted the social roles of woman only to house and family affairs, particularly whether their argument is based on genuine and absolute evidence (qat`i al-dalalah wa al-thubut) from the Qur’an, or based on ijtihad. Finally, their views are assessed through and within the Qur’anic teachings on social responsibility and also through woman’s social status during the time of the Prophet p.b.u.h..